Enterobacter hormaechei KIMS8 and Enterobacter cloacae KIMS10 isolated from Kapuas River, Kalimantan, Indonesia as indigenous multi-resistant bacteria to copper and dyes - WAHYU IRAWATI; MICHAEL TIMOTHY; SAMUEL EMMANUEL SOENTORO; REINHARD PINONTOAN; TRIWIBOWO YUWONO; VALENTINE LINDARTO (Society for Indonesian Biodiversity, 2022)
Abstract. Irawati W, Timothy M, Soentoro SE, Pinontoan R, Yuwono T, Lindarto V. 2022. Enterobacter hormaechei KIMS8 and Enterobacter cloacae KIMS10 isolated from Kapuas River, Kalimantan, Indonesia as indigenous multi-resistant bacteria to copper and dyes. Biodiversitas 23: 6661-6668. Study on the characterization of multiple copper and dyes resistance in bacteria has so far been quite limited. It is, therefore, of interest to isolate and characterize such bacteria. The study was aimed to isolate bacteria from the Kapuas River in Indonesia and measuring copper resistance as well as dye-resistance and decolorization abilities. Copper resistance was determined by measuring the minimum inhibitory concentration (MIC) of copper, while dye-resistance was measured by observing changes in colony color and clear zone formation and decolorization ability was determined by spectrophotometry. It was found that 2 out of the 15 isolated strains showed the highest copper resistance with the MIC of 7 mM. The two bacterial strains KIMS8 and KIMS10, were grown in solid media supplemented with 300 ppm of methylene blue or reactive black dye. Bacterial decolorization assays showed that KIMS8 was able to decolorize up to 90% methylene dye and up to 11.3% of reactive black dye whereas KIMS10 was able to decolorize 94.9% of methylene blue dye and 12.1% of reactive black dye. Molecular characterization by 16S rRNA gene sequencing of these two strains showed that KIMS8 and KIMS10 were identified as Enterobacter hormaechei and E. cloacae, respectively.